Multi-layer golf ball with large diameter inner core
The multi-layer golf ball design with a large diameter inner core, thin outer core, and appropriate cover materials addresses the challenges of rebound performance, durability, and spin control, resulting in improved distance and accuracy.
Patent Information
- Application Number
- JP2021179911
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-13
- Filing Date
- 2021-11-04
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-11-04
AI Technical Summary
Existing golf balls face challenges in achieving optimal rebound performance, durability, and spin control, which are crucial for distance and accuracy in golf shots.
A multi-layer golf ball design featuring a core assembly with a large diameter inner core and a thin outer core layer, both made from thermosetting or thermoplastic compositions, and a cover layer composed of ethylene acid copolymer or polyurethane materials.
The design enhances rebound performance, durability, and spin control, allowing for greater distance and improved shot accuracy, while also providing a softer feel for better player control.
Smart Images

Figure 0007660484000008 
Figure 0007660484000009 
Figure 0007660484000010
Abstract
Description
[Technical field]
[0001] The present invention generally relates to a multi-piece golf ball having a core with at least one layer and a cover with at least one layer. The inner core layer preferably has a thermoset or thermoplastic composition and has a relatively large diameter. The outer core layer preferably has a thermoset or thermoplastic composition and has a relatively small diameter. [Background technology]
[0002] Both professional and amateur golfers use multi-piece solid golf balls today. Essentially, two-piece solid golf balls include a solid inner core protected by an outer cover. The inner core is made from natural rubber or synthetic rubbers such as polybutadiene, styrene butadiene, polyisoprene, etc. The cover surrounds the inner core and may be made from a variety of materials such as ethylene copolymer ionomers, polyamides, polyesters, polyurethanes, polyureas, etc.
[0003] In recent years, three-piece, four-piece, and even five-piece balls have become more common. These multi-piece balls have become popular for several reasons, including new manufacturing techniques, reduced material costs, and desirable ball playing performance characteristics. Many golf balls in use today have a multi-layer core, including an inner core and at least one surrounding outer core layer. For example, the inner core may be made of a relatively soft, resilient material, and the outer core may be made of a harder, more rigid material. The "dual core" subassembly is then encapsulated with a single or multi-layer cover to achieve the final ball assembly. Various materials may be used to manufacture the core and cover to impart desired properties to the finished ball.
[0004] In general, dual cores having an inner core (or center) and a surrounding outer core layer are known in the industry. For example, U.S. Patent No. 6,390,935 (Sugimoto) discloses a three-piece golf ball having a core with a center and an outer shell, and a cover disposed around the core. The specific gravity of the outer shell is greater than that of the center. The center has a JIS-C hardness (X) at the center point and a JIS-C hardness (Y) at the surface point, satisfying the formula (YX)>8. The core structure (center and outer shell) has a JIS-C hardness (Z) of 80 or more at the surface. The cover has a Shore D hardness of less than 60.
[0005] U.S. Patent No. 6,520,872 (Endo) discloses a three-piece golf ball including a center, an intermediate layer formed on the center, and a cover formed on the intermediate layer, the center preferably being made of a high cis polybutadiene rubber, and the intermediate layer and the cover layer preferably being made of an ionomer resin such as an ethylene acid copolymer.
[0006] U.S. Patent No. 7,160,208 (Watanabe) discloses a three-piece golf ball having a rubber-based inner core, a rubber-based outer core layer, and a cover based on a polyurethane elastomer. The inner core has a JIS-C hardness of 50 to 85, the outer core layer has a JIS-C hardness of 70 to 90, and the cover has a Shore D hardness of 46 to 55. The inner core has a specific gravity of 1.0 or more, and the outer layer of the core has a specific gravity equal to or greater than the specific gravity of the inner core.
[0007] The core structure is the engine or spring of the golf ball. Thus, the composition and structure of the core are key factors in determining the elasticity and rebound performance of the ball. Generally, the rebound performance of a ball is determined by calculating the initial velocity after hitting the face of a golf club and the outward velocity after impacting a hard surface. More specifically, the "coefficient of restitution" or "COR" of a golf ball refers to the ratio of the rebound velocity of the ball to its initial input velocity when the ball is fired from an air cannon onto a rigid vertical plate. The COR of a golf ball is written as a decimal value ranging from 0 to 1. Golf balls may have different COR values at different initial velocities. Since the United States Golf Association (USGA) places limits on the initial velocity of the ball, one of the objectives of golf ball manufacturers is to maximize the COR under such conditions. The higher the rebound velocity of a ball, the higher the COR value. Such golf balls will rebound faster, retain more total energy when struck by a club, and fly longer, as opposed to balls with lower COR values. These characteristics are especially important for long-distance shots. For example, a ball with a high resilience and COR value tends to travel farther when hit with a driver club off the tee.
[0008] The durability, spin rate, and feel of a ball are also important characteristics. In general, the durability of a ball refers to the impact resistance of the ball. A ball with low durability appears worn and damaged even after a short period of use. In some cases, the cover may crack or tear. Spin rate refers to the speed at which the ball spins after being struck by a club. A ball with a relatively high spin rate is advantageous for short-distance shots made with irons and wedges. Professional golfers and highly skilled amateur golfers can impart backspin to such balls more easily. This allows the player to better control the ball and improve the accuracy and placement of the shot. By putting the right amount of spin on the ball, the player can stop the ball accurately on the green or fade the ball during an approach shot. On the other hand, recreational players who cannot intentionally control the spin of the ball when hitting it with a club are less likely to use a high spin ball. For such players, the ball is more likely to spin sideways and drift farther off the course, especially if it is hooked or sliced. The "feel" of a ball generally refers to the sensation felt when hitting the ball with a club and is a difficult characteristic to quantify. Most players prefer softer feeling balls because players experience a more natural and comfortable sensation when the club face makes contact with these balls. Softer feeling balls are especially desirable when taking short shots around the green because players feel more with such balls. The feel of a ball depends primarily on the hardness and compression of the ball.
[0009] Golf ball manufacturers are constantly searching for different materials to improve the playing performance and other characteristics of the balls, and the present invention provides golf balls having advantageous properties and characteristics.
[0010] Golf ball manufacturers are constantly searching for different materials to improve the playing performance and other characteristics of the balls, and the present invention provides golf balls having advantageous properties and characteristics. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] U.S. Patent No. 6,390,935 [Patent Document 2] U.S. Patent No. 6,520,872 [Patent Document 1] U.S. Patent No. 7,160,208 Summary of the Invention
[0012] The present invention relates generally to multi-layer golf balls, and more specifically to golf balls having an inner core with a relatively large diameter. In one embodiment, the golf ball includes a core assembly and a cover having at least one layer. The core assembly includes a) an inner core having a thermoset or thermoplastic composition, the inner core having an inner core diameter (ICD) in the range of about 1.2 to about 1.5 inches, an outer surface hardness (H) of about 1.2 to about 1.5 inches, and a cover having a relatively large diameter. inner core surface ), center hardness (H inner core center ), an inner core volume (ICV), and an inner core compression (ICC); and b) an outer core layer having a thermosetting or thermoplastic composition disposed about the inner core, the outer core layer having a thickness ranging from about 0.05 to about 0.2 inches such that the overall core assembly has a total core diameter (TCD) of between about 1.5 to about 1.6 inches, the outer core having an outer surface hardness (H outer surface of OC ), center point hardness (H midpoint of OC ), an outer core volume (OCV), and a total core compression (TCC), wherein the ICV is greater than the OCV, and the core assembly has a core profile of about 1.8 or greater, where (inner core diameter / total core diameter) x (total core compression / inner core compression) = core profile.
[0013] In one embodiment, the core profile is greater than 2.0, and in another embodiment, the core profile is greater than 3.0. The OCV may have a value less than or equal to a value X, where X is calculated according to the formula: (0.9)(ICV)=X. The TCC may have a value greater than or equal to a value Y, where Y is calculated according to the formula: (2.0)(ICC)=Y.
[0014] The inner core and the outer core may each have a rubber composition selected from the group consisting of polybutadiene, polyisoprene, ethylene-propylene, ethylene-propylene-diene, styrene-butadiene, and polyalkenamer rubbers, and mixtures thereof. Preferably, a blend of polybutadiene rubbers is employed to form the inner core.
[0015] In one embodiment, H inner core surface H inner core center so as to achieve a positive hardness gradient across the inner core, and outer surface of OC is H midpoint of OC In one embodiment, H outer surface of OC is H inner core center The inner core has a diameter of about 1.39 inches and the overall core assembly has a diameter of about 1.55 inches. In another embodiment, the inner core has a diameter of about 1.25 inches and the overall core assembly has a diameter of about 1.55 inches. In one embodiment, the inner core has a compression in the range of about 20 to about 50 and the overall core assembly has a compression in the range of about 60 to 110.
[0016] In one embodiment, the cover is a single layer and comprises an ethylene acid copolymer containing acid groups such that less than 70% of the acid groups are neutralized. For example, the cover comprises a blend of a sodium neutralized ethylene acid copolymer and a lithium neutralized ethylene acid copolymer. In another embodiment, the cover comprises an inner cover layer and an outer cover layer, the inner cover layer comprises an ethylene acid copolymer containing acid groups such that less than 70% of the acid groups are neutralized, and the outer cover layer is selected from the group consisting of polyurethanes, polyureas, polyurethane-urea hybrids, and copolymers and blends thereof. Preferably, the outer cover comprises a thermoplastic or thermoset polyurethane. [Brief description of the drawings]
[0017] The novel technology which characterizes the present invention is set forth in the appended claims, however the preferred embodiments of the invention, together with further objects and attendant advantages, will best be understood by reference to the following detailed description taken in conjunction with the accompanying drawings, in which: [Figure 1] 1 is a cross-sectional view of a core assembly of a golf ball made in accordance with the present invention. [Diagram 2] 1 is a cross-sectional view of a three-piece golf ball having a two-layer core assembly and a single layer cover made in accordance with the present invention. [Diagram 3] 1 is a cross-sectional view of a four-piece golf ball having a two-layer core assembly and a two-layer cover made in accordance with the present invention. [Figure 4] FIG. 1 is a perspective view of a dimpled golf ball made in accordance with the present invention; Detailed Description of the Invention
[0018] In accordance with the present invention, golf balls of various constructions may be produced. For example, golf balls having two-piece, three-piece, and four-piece constructions with single or multiple layers of cover material may be produced. Representative diagrams of such golf ball constructions are provided and further discussed below. The term "layer" as used herein generally refers to any spherical portion of a golf ball. More specifically, in one version, a two-piece golf ball is produced that includes a core with a surrounding cover. Three-piece golf balls may be produced that include a two-layer core and a single-layer cover. A dual core includes an inner core (center) and a surrounding outer core layer. In another version, a four-piece golf ball is produced that includes a dual core and a dual cover (inner cover and outer cover layers). In yet another construction, a four-piece or five-piece golf ball may be produced that includes a dual core, casing layer(s), and cover layer(s). As used herein, the term "casing layer" refers to a layer of the ball that is disposed between the multi-layer core assembly and the cover. The casing layer may also be referred to as a mantle or intermediate layer. The diameters and thicknesses of the different layers, along with properties such as hardness and compression, may vary depending on the golf ball construction and desired playability characteristics, as further described below.
[0019] Core Structure The golf ball may include a single layer or multiple layer core. In one preferred embodiment, a core assembly is produced that includes an inner core (center) and a surrounding outer core layer. Thermosetting or thermoplastic compositions may be used to form the inner and outer core layers. In one preferred embodiment, at least one of the core layers is formed from a rubber composition. Preferably, the rubber composition comprises polybutadiene rubber. More specifically, in one version, the ball includes a dual core having an inner core (center) and a surrounding outer core layer, each layer being made from a polybutadiene rubber composition.
[0020] Suitable rubber compositions for forming at least one of the core layers include, but are not limited to, rubber compositions including rubber materials such as polybutadiene, ethylene propylene rubber, ethylene propylene diene rubber, polyisoprene, styrene butadiene rubber, polyalkenamers, butyl rubber, halobutyl rubber, or polystyrene elastomers. For example, a thermosetting rubber composition including polybutadiene rubber may be used to form both the inner core (center) and the surrounding outer core layer in a dual-layer structure. In another version, at least one of the core layers is formed from a thermoplastic composition. For example, an ionomer composition including an ethylene acid copolymer (partially neutralized polymer) containing acid groups such that less than 70% of the acid groups are neutralized may be used. In another example, an ionomer composition including an ethylene acid copolymer (highly neutralized polymer or HNP) containing acid groups such that more than 70% of the acid groups are neutralized may be used. For example, a thermoplastic ionomer composition may be used to form both the inner core (center) and the surrounding outer core layer in a dual-layer structure. In another example, a thermoset rubber composition may be used to form the inner core and a thermoplastic ionomer composition may be used to form the outer core. In yet another example, a thermoplastic ionomer composition may be used to form the inner core and a thermoset rubber composition may be used to form the outer core layer. Such rubber and ionomer compositions are discussed in more detail below.
[0021] Generally, polybutadiene is a homopolymer of 1,3-butadiene. The double bonds in the 1,3-butadiene monomer are attacked by a catalyst to grow the polymer chain and form a polybutadiene polymer with the desired molecular weight. Depending on the desired properties, any suitable catalyst may be used to synthesize polybutadiene rubber. Typically, the catalyst is a transition metal complex (e.g., neodymium, nickel, cobalt) or an alkyl metal such as an alkyl lithium. Other catalysts include, but are not limited to, aluminum, boron, lithium, titanium, and combinations thereof. The catalyst produces polybutadiene rubber with different chemical structures. In the cis bond configuration, the main internal polymer chains of the polybutadiene appear on the same side of the carbon-carbon double bond contained in the polybutadiene. In the trans bond configuration, the main internal polymer chains are on the opposite side of the internal carbon-carbon double bond in the polybutadiene. Polybutadiene rubber can have various combinations of cis and trans bond structures. Preferred polybutadiene rubbers have a 1,4 cis content of at least 40%, preferably greater than 80%, more preferably greater than 90%. Generally, polybutadiene rubbers with a high 1,4 cis content have high tensile strength. Polybutadiene rubbers may have a relatively high Mooney viscosity or a low Mooney viscosity.
[0022] Examples of commercially available polybutadiene rubbers that may be utilized in accordance with the present invention include, but are not limited to, BR01 and BR1220 available from BST Elastomers, Bangkok, Thailand; SE BR1220LA, and SE BR1203 available from DOW Chemical Company, Midland, Michigan; BUDENE 1207, 1207s, 1208, and 1280 available from Goodyear Company, Akron, Ohio; BR 01, 51, and 730 available from Japan Synthetic Rubber Co. (JSR), Tokyo, Japan; Buna CB21, CB22, CB23, CB24, CB25, CB29 available from Lanxess Corporation, Pittsburgh, Pennsylvania. MES, CB60, CBNd60, CB55NF, CB70B, CBKA8967, and CB1221; BR1208 available from LG Chemical Co., Seoul, Korea; UBEPOL BR130B, BR150, BR150B, BR150L, BR230, BR360L, BR710, and BCR617 available from UBE Industry Co., Ltd., Tokyo, Japan; EUROPRENE NEOCIS BR60, INTENE 60AF, and P30AF available from Polimeri Europa, Rome, Italy; AFDENE 50 and NEODENE BR40, BR45, BR50, and BR60 available from Karbochem (PTY) Ltd., Bruma, South Africa; and KBR available from Kumho Petrochemical Co., Seoul, Korea. 01, NdBr40, NdBr-45, NdBr60, KBR710S, KBR710H, and KBR750, as well as DIENE 55NF, 70AC, and 320AC available from Firestone Polymers, Inc., Akron, Ohio.
[0023] To form the core, the polybutadiene rubber is used in an amount of at least about 5% by weight based on the total weight of the composition, generally ranging from about 5% to about 100% by weight of the composition, or having a lower limit of 5% or 10% or 20% or 30% or 40% or 50% and an upper limit of 55% or 60% or 70% or 80% or 90% or 95% or 100%. Generally, the concentration of polybutadiene rubber is about 45 to about 95% by weight. Preferably, the rubber material used to form the core layer comprises at least 50% by weight, more preferably at least 70% by weight of polybutadiene rubber.
[0024] The rubber composition of the present invention may be cured using conventional curing processes, either by pre-blending or post-blending. Suitable curing processes include, for example, peroxide curing agents, sulfur curing agents, high energy radiation, and combinations thereof. Preferably, the rubber composition includes a free radical initiator selected from an organic peroxide, a high energy radiation source capable of generating free radicals, and combinations thereof. In one preferred version, the rubber composition is peroxide cured. Suitable organic peroxides include, but are not limited to, dicumyl peroxide; n-butyl-4,4-bis(t-butylperoxy)valerate; 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane; 2,5-dimethyl-2,5-di(t-butylperoxy)hexane; di-t-butyl peroxide; di-t-amyl peroxide; t-butyl peroxide; t-butylcumyl peroxide; 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3; di(2-t-butyl-peroxyisopropyl)benzene; dilauryl peroxide; dibenzoyl peroxide; t-butyl hydroperoxide; and combinations thereof. In a preferred embodiment, the free radical initiator is dicumyl peroxide, which is commercially available, but is not limited to, Perkadox™ BC from Akzo Nobel. Peroxide free radical initiators are generally present in rubber compositions in an amount of at least 0.05 parts by weight per 100 parts by weight of total rubber, or in an amount within a range having a lower limit of 0.05 parts by weight or 0.1 parts by weight or 1 parts by weight or 1.25 parts by weight or 1.5 parts by weight or 2.5 parts by weight or 5 parts by weight per 100 parts by weight of total rubber and an upper limit of 2.5 parts by weight or 3 parts by weight or 5 parts by weight or 6 parts by weight or 10 parts by weight or 15 parts by weight per 100 parts by weight of rubber. Concentrations are given in parts per hundred (phr) unless otherwise indicated. As used herein, the term "parts per hundred," also known as "phr" or "pph," is defined as the number of parts by weight of a particular component present in a mixture per 100 parts by weight of polymer.Mathematically, this can be expressed as the weight of the component divided by the total weight of the polymer multiplied by 100.
[0025] The rubber composition preferably includes a reactive crosslinking coagent. Suitable coagents include, but are not limited to, metal salts of unsaturated carboxylic acids having 3 to 8 carbon atoms; unsaturated vinyl compounds and polyfunctional monomers (e.g., trimethylolpropane trimethacrylate); phenylene bismaleimide; and combinations thereof. Specific examples of suitable metal salts include, but are not limited to, one or more metal salts of acrylates, diacrylates, methacrylates, and dimethacrylates, where the metal is selected from magnesium, calcium, zinc, aluminum, lithium, and nickel. In a specific embodiment, the coagent is selected from zinc salts of acrylates, diacrylates, methacrylates, and dimethacrylates. In another specific embodiment, the agent is zinc diacrylate (ZDA). When the coagent is zinc diacrylate and / or zinc dimethacrylate, the coagent is typically included in the rubber composition in an amount within the range of a lower limit of 1 or 5 or 10 or 15 or 19 or 20 parts by weight per 100 parts by weight of total rubber, and an upper limit of 24 or 25 or 30 or 35 or 40 or 45 or 50 or 60 parts by weight per 100 parts by weight of the base rubber.
[0026] Free radical scavengers such as halogenated organic sulfur, organic disulfide, or inorganic disulfide compounds may be added to the rubber composition. These compounds may function as "softening and speed-up agents." As used herein, "softening and speed-up agents" refers to any agent or blend thereof that can make the core (1) softer at a given "coefficient of restitution" (COR) and / or (2) faster (gain a higher COR at equal compression) when compared to a core prepared permeably without the softening and speed-up agent. Preferred halogenated sulfur compounds include, but are not limited to, pentachlorothiophenol (PCTP) and salts of PCTP, such as ZnPCTP. Employing PCTP and ZNPCTP in the inner core of a golf ball achieves a soft and fast inner core. PCTP and ZnPCTP compounds help increase the elasticity and coefficient of restitution of the core. In specific embodiments, the softening and speeding up agents are ZnPCTP, PCTP, ditolyl disulfide, diphenyl disulfide, dixylyl disulfide, 2-nitroresorcinol and combinations thereof.
[0027] The rubber composition of the present invention may include a filler, which is added to adjust the density and / or specific gravity of the material. Suitable fillers include, but are not limited to, polymeric or mineral fillers, metal fillers, metal alloy fillers, metal oxide fillers, and carbonaceous fillers. The filler may be in any suitable form, including, but not limited to, flakes, fibers, whiskers, fibrils, plates, particles, and powders. Rubber regrind is a ground, recycled material (e.g., ground to about 30 mesh particle size) obtained from discarded rubber golf balls, which can also be used as a filler. The amount and type of filler employed is determined by the amount and weight of other ingredients in the golf ball, since a maximum golf ball weight of 45.93 g (1.62 oz) is set by the United States Golf Association (USGA).
[0028] Suitable polymeric or mineral fillers that may be added to the rubber composition include, for example, precipitated hydrated silica, clay, talc, asbestos, glass fibers, aramid fibers, mica, calcium metasilicate, zinc sulfate, barium sulfate, zinc sulfide, lithopone, silicates, silicon carbide, diatomaceous earth, polyvinyl chloride, carbonates such as calcium carbonate and magnesium carbonate. Suitable mineral fillers include titanium, tungsten, aluminum, bismuth, nickel, molybdenum, iron, lead, copper, boron, cobalt, beryllium, zinc, and tin. Suitable metal alloys include steel, brass, bronze, boron carbide whiskers, and tungsten carbide whiskers. Suitable metal oxide fillers include zinc oxide, iron oxide, aluminum oxide, titanium dioxide, magnesium oxide, and zirconium oxide. Suitable particulate carbonaceous material fillers include graphite, carbon black, cotton flock, natural bitumen, cellulose flock, and leather fibers. Microballoon fillers such as glass and ceramic, and fly ash fillers may also be used. In a specific aspect of this embodiment, the rubber composition includes a filler selected from carbon black, nanoclays (e.g., Cloisite™ and Nanofil™ nanoclays commercially available from Southern Clay Products, Nanomax™ and Nanomer™ nanoclays commercially available from Nanocor), talc (e.g., LuzenacHAR™ high aspect ratio talc commercially available from Luzenac America), glass (e.g., glass flake, ground glass, and microglass), mica and mica-based pigments (e.g., Iriodin fluorescent pigments commercially available from The Merck Group), and combinations thereof. In a specific embodiment, the rubber composition is modified with organic fiber micropulp.
[0029] Additionally, the rubber composition may include an antioxidant to prevent degradation of the elastomer. Also, processing aids such as high molecular weight organic acids and their salts may be added to the composition. In specific embodiments, the total amount of additives and fillers present in the rubber composition is 15% by weight or less, or 12% by weight or less, or 10% by weight or less, or 9% by weight or less, or 6% by weight or less, or 5% by weight or less, or 4% by weight or less, or 3% by weight or less, based on the total weight of the rubber composition.
[0030] The polybutadiene rubber material (base rubber) may be blended with other elastomers in accordance with the present invention. Other elastomers include, but are not limited to, polybutadiene, polyisoprene, ethylene propylene rubber ("EPR"), ethylene-propylene-diene ("EPDM") rubber, styrene-butadiene rubber, styrene block copolymer rubber (e.g., "SI", "SIS", "SB", "SBS", "SIBS", etc., where "S" is styrene, "I" is isobutylene, and "B" is butadiene), polyalkenamers such as polyoctenamers, butyl rubber, halobutyl rubber, polystyrene elastomers, polyethylene elastomers, polyurethane elastomers, polyurea elastomers, metallocene catalyzed elastomers and plastomers, copolymers of isobutylene and p-alkylstyrene, halogenated copolymers of isobutylene and p-alkylstyrene, copolymers of butadiene with acrylonitrile, polychloroprene, alkyl acrylate rubbers, chlorinated isoprene rubbers, acrylonitrile chlorinated isoprene rubbers, and combinations of two or more thereof. In one preferred embodiment, the inner core comprises a blend of a) a first polybutadiene rubber and b) a second polybutadiene rubber, the first and second polybutadiene rubbers being produced using different catalysts. Preferred catalysts include those selected from the group consisting of neodymium, nickel, cobalt, aluminum, boron, lithium, titanium, and combinations thereof.
[0031] In accordance with the present invention, the polymer, free radical initiator, filler, crosslinking agent, and any other materials used to form any portion of the center or core of the golf ball may be combined and formed into a mixture using any type of mixing technique known to those skilled in the art. Suitable types of mixing include single pass and multi-pass mixing, etc. Crosslinking agents, and any other optional additives used to modify the properties of the center or additional layers of the golf ball may be similarly combined by any type of mixing technique. A single pass mixing process in which ingredients are added sequentially is preferred because this type of mixing tends to increase the efficiency of the process and reduce costs. A preferred mixing cycle is a single step in which the polymer, cis-trans catalyst, filler, zinc diacrylate, and peroxide are added sequentially.
[0032] In one preferred embodiment, the entire core or at least one core layer of the multi-layer structure is formed from a rubber composition including, but not limited to, polybutadiene, polyisoprene, ethylene propylene rubber ("EPR"), ethylene-propylene-diene ("EPDM") rubber, styrene-butadiene rubber, styrenic block copolymer rubber (such as "SI", "SIS", "SB", "SBS", "SIBS", etc., where "S" is styrene, "I" is isobutylene, and "B" is butadiene), polyalkenamers, such as polyoctenamers, butyl rubbers, and the like. The rubbers may include materials selected from the group of natural and synthetic rubbers including butadiene, alkyl acrylate rubbers, halobutyl rubbers, polystyrene elastomers, polyethylene elastomers, polyurethane elastomers, polyurea elastomers, metallocene catalyzed elastomers and plastomers, copolymers of isobutylene and p-alkylstyrene, halogenated copolymers of isobutylene and p-alkylstyrene, copolymers of butadiene with acrylonitrile, polychloroprene, alkyl acrylate rubbers, chlorinated isoprene rubbers, acrylonitrile chlorinated isoprene rubbers, and combinations of two or more thereof.
[0033] As discussed above, single-layer and multi-layer cores can be made according to the invention. In a two-layer core, the outer core layer can be made of a thermosetting material, such as a thermosetting rubber, and the outer core layer can be made of a thermoplastic material, such as an ethylene acid copolymer, in which the acid groups are at least partially or fully neutralized. Suitable ionomer compositions include partially neutralized ionomers and fully neutralized ionomers, including blends of two or more partially neutralized ionomers, blends of two or more highly neutralized ionomers (HNP), and ionomers formed from blends of one or more partially neutralized ionomers with one or more highly neutralized ionomers.
[0034] Some examples of suitable thermoplastic ionomers that can be used in accordance with the present invention include DuPont® HPF EXX 367, HPF 1000, HPF 2000, HPF AD1035, HPF AD1035 Soft, HPF AD1040, and AD1172 ionomers commercially available from EI du Pont de Nemours and Company. The coefficient of restitution ("COR"), compression, and surface hardness of these materials, as measured on 1.55 inch injection molded balls aged for 2 weeks at 23°C / 50% RH, are set forth below in Table 1. Other suitable ethylene acid copolymer ionomers and other thermoplastics that can be used to form the core layer are the same materials that can be used to make the inner and outer cover layers, as described further below.
[0035] [Table 1]
[0036] As shown in FIG. 1, the core assembly (14) has a relatively large diameter inner core (16) and a surrounding relatively thin outer core layer (18). As shown in FIG. 2, in one embodiment, a golf ball (20) has a core with a dual layer construction including an inner core layer (22) preferably made of a polybutadiene rubber composition, and an outer core layer (24) preferably made of a thermosetting or thermoplastic composition, and a surrounding cover (26). In another embodiment, the inner core (22) is formed from a thermosetting or thermoplastic composition, and the outer core (24) is formed from a polybutadiene rubber composition. Another embodiment of a golf ball is shown in FIG. 3, in which a four-piece golf ball (29) includes a dual core (30) having an inner core (30a) and an outer core layer (30b). The dual core is surrounded by a multi-layer cover with an inner cover layer (32a) and an outer cover layer (32b). 4, a front view of a finished golf ball, generally designated 10, that may be manufactured in accordance with the present invention is shown. The dimples 12 may have a variety of shapes and be arranged in a variety of patterns to modify the aerodynamic characteristics of the ball. The dimples 12 may have a variety of shapes and be arranged in a variety of patterns to modify the aerodynamic characteristics of the ball.
[0037] As shown in Figures 1-4 and discussed above, the core structure of the present invention can be used to produce a variety of ball structures. Such golf ball structures include, for example, five-piece and six-piece structures. It should be noted that the golf balls shown in Figures 1-4 are for illustrative purposes only and are not limiting. Other golf ball structures can be produced in accordance with the present invention.
[0038] Inner Core Dimensions The Royal and Ancient Golf Club of St. Andrews in Scotland (R&A Rules Limited) and the United States Golf Association (USGA) have established standards for the weight, size, and other characteristics of golf balls. For example, the R&A and USGA have established a maximum weight of 1.62 ounces (45.93 grams) and a minimum size (diameter) of 1.68 inches. When played outside the rules of the R&A and USGA, golf balls can be heavier and smaller in size.
[0039] In some embodiments, the golf balls of the invention are manufactured in accordance with the requirements of the R&A and the USGA and have conforming weights, sizes, and other characteristics. In other embodiments, the golf balls of the invention are manufactured outside the requirements of the R&A and the USGA and have non-conforming weights, sizes, and / or other characteristics.
[0040] Specifically, the Royal and Ancient Golf Club of St. Andrews, Scotland (R&A Rules Limited) and the United States Golf Association (USGA) rules require that the diameter of a ball may not be greater than 1.680 inches (42.67 mm). As used herein, the term "non-conforming diameter" or "non-conforming size" means that the ball has a diameter less than 1.680 inches. For example, in some embodiments, the ball may have a non-conforming diameter, for example, in the range of about 1.480 to less than 1.680 inches. In other embodiments, the ball may have a conforming diameter size greater than 1.680 inches. That is, there is no maximum size requirement. A ball may have a diameter greater than 1.680 inches and still be considered a "conforming" ball. These balls are often referred to as "oversized" balls. Thus, in one example, the ball has a diameter size greater than 1.680 inches, ranging up to about 2.080 inches.
[0041] Preferably, the inner core is relatively large in volume. For example, the inner core preferably comprises at least 60% of the total volume of the core subassembly, and more preferably at least 70% of the total volume of the core subassembly. Typically, the inner core may have a diameter within the range of about 1.10 to about 1.62 inches. Preferably, the inner core has a diameter size with a lower limit of about 1.10 or 1.15 or 1.20 or 1.25 or 1.30 inches and an upper limit of about 1.40 or 1.45 or 1.50 or 1.55 or 1.62 inches. In one preferred embodiment, the inner core has a diameter in the range of about 1.10 to about 1.50 inches, and more preferably, about 1.25 to about 1.45 inches. For example, in one version, the diameter of the inner core structure is about 1.40 inches. Meanwhile, the outer core layer typically has a thickness within the range of about 0.05 to about 0.4 inches. Preferably, the outer core has a thickness with a lower limit of about 0.05 or 0.06 or 0.08 or 0.10 inches and an upper limit of 0.20 or 0.25 or 0.30 or 0.35 or 0.40 inches. In one preferred embodiment, the outer core layer has a thickness ranging from about 0.05 to about 0.20 inches, more preferably from about 0.08 to about 0.15 inches. Thus, the bilayer core structure preferably has an overall diameter within the range of about 1.50 to about 1.60 inches. For example, in one version, the overall diameter of the bilayer core structure is about 1.55 inches. In another example, the bilayer core structure has an overall diameter of about 1.58 inches.
[0042] Bilayer core structures containing layers having various diameters, thicknesses and volume dimensions may be manufactured in accordance with the present invention. Some examples of core structures containing layers of various diameters, thicknesses and volumes are set forth in Tables 2 and 2A below. [Table 2] [Table 3] (Notes) * Cms: centimeters ** cubic inch *** cub cms: cubic centimeters 1 The volume of the inner core is given by the formula: V = (4 / 3)πr 3 is determined in accordance with 2 The volume of the outer A is determined according to the following formula: Total volume of core - volume of inner core = volume of outer core 3 The total volume of the core assembly is determined according to the following formula: V = (4 / 3)πr 3
[0043] The core structure of the present invention provides the golf ball with many advantageous mechanical and playability characteristics. Specifically, the core structure of the present invention has a particular relationship between the dimensions of the core layer and the compression, which is referred to herein as the "core profile" and will be described in more detail below. Preferably, the entire core assembly has a core profile of about 1.8 or greater. The golf balls of the present invention are particularly advantageous because they have a relatively large inner core (center) and a relatively thin outer core layer. In one preferred embodiment, the inner core has a diameter of 1.39 inches and the entire core assembly has a diameter of 1.55 inches. Preferably, the inner core has a coefficient of restitution (COR) of at least 0.78 and the entire core assembly has a COR of at least 0.80. The finished golf ball preferably has a COR of at least 0.80. The inner core of the golf ball preferably has a compression in the range of about 20 to about 50, and the compression of the entire core assembly preferably ranges from about 60 to about 110. The finished golf balls preferably have a compression of between about 70 and 110.
[0044] These features and characteristics allow a player to generate greater ball speeds off the tee and achieve greater distances using a driver. When a driver club is hit off the tee, the ball tends to travel farther. At the same time, the spin rate and launch angle of the ball are not controlled by the driver. Spin rate refers to the rotational speed of the ball after it is struck by the club. Launch angle is the angle with respect to the ground that the ball leaves after the club head is struck. The overall trajectory of the ball is then determined by the initial launch conditions and the aerodynamic characteristics of the ball. A ball with a relatively high spin rate may be difficult to control on drives and result in shorter distances, especially for recreational players. For such players, the backspin has an angled axis and is prone to forming a lateral lift that causes the ball to drift farther away from the intended direction. In this invention, the ball can be designed to have a higher driver speed, a higher launch angle, and a lower driver spin off the tee. Thus, the ball can travel farther and the flight path of the ball can be more easily controlled. This speed and control allows the player to make better driver shots.
[0045] Core Profile As previously discussed, the core structure of the present invention provides a number of advantageous properties to the ball. Specifically, the core structure has a particular relationship between the dimensions of the core layer and the compression of the core layer, which is referred to herein as the "core profile" and is further described in Tables 3 and 4 below. [Table 4] * Core profile is calculated based on formula 1 Formula 1: (Inner core diameter / total core diameter) x (total core compression / inner core compression) = core profile [Table 5] * Core profile is calculated based on formula 1
[0046] In accordance with the present invention, the golf ball preferably has a core assembly including: a) an inner core having a thermoset or thermoplastic composition, the inner core having an inner core diameter (ICD) ranging from about 1.2 to about 1.5 inches, an outer surface hardness (H inner core surface ), center hardness (H inner core center ), an inner core volume (ICV), and an inner core compression (ICC); and b) an outer core layer having a thermosetting or thermoplastic composition disposed about the inner core, the outer core layer having a thickness ranging from about 0.05 to about 0.2 inches such that the overall core assembly has a total core diameter (TCD) of between about 1.5 to about 1.6 inches, the outer core having an outer surface hardness (H outer surface of OC ), center point hardness (H midpoint of OC ), an outer core volume (OCV), and a total core compression (TCC), the ICV being greater than the OCV, and the core assembly having a core profile of about 1.8 or greater. In another preferred embodiment, the core profile is greater than 2.0. In yet another preferred embodiment, the core profile is greater than 3.0. In one preferred embodiment, the OCV may have a value less than or equal to a value X, where X is calculated according to the formula: (0.9)(ICV)=X. Thus, in this example, if the inner core volume (ICV) is 0.9 cubic inches, the outer core volume (OCV) is less than or equal to 0.81. In another preferred embodiment, the TCC may have a value greater than or equal to a value Y, where Y is calculated according to the formula: (2.0)(ICC)=Y. Thus, in this example, if the inner core compression (ICC) is 40 DCM, the total core compression (TCC) will be greater than or equal to about 80 DCM.
[0047] Inner core hardness The hardness of the core subassembly (inner core and outer core layer) is an important characteristic. In general, cores with relatively high hardness values tend to have high compression and good durability and resilience. However, some highly compressed balls are hard, which can negatively affect shot control and placement. Therefore, an optimal balance of hardness in the core assembly must be achieved. The present invention provides a core assembly with both good CoR and compression characteristics. Generally, a more resilient core will have higher velocity and travel a longer distance when struck with a golf club. The "feel" of the ball is also important, which generally refers to the sensation a player feels when striking the ball with a club. Ball feel is a difficult characteristic to quantify. Most players prefer softer feeling balls because players experience a more natural and comfortable sensation when the club face makes contact with these balls. The feel of the ball depends primarily on the hardness and compression of the ball.
[0048] In one preferred golf ball, the inner core (center) has a "positive" hardness gradient (i.e., the outer surface of the inner core is harder than its geometric center) and the outer core layer has a "positive" hardness gradient (i.e., the outer surface of the outer core layer is harder than the inner surface of the outer core layer). In such cases where both the inner and outer core layers each have a "positive" hardness gradient, the outer surface hardness of the outer core layer is preferably greater than the hardness of the geometric center of the inner core.
[0049] In another version, the inner core may have a positive hardness gradient, and the outer core layer may have a "zero" hardness gradient (i.e., the hardness values of the outer surface of the outer core layer and the inner surface of the outer core layer are substantially the same) or a "negative" hardness gradient (i.e., the outer surface of the outer core layer is softer than the inner surface of the outer core layer). In a second alternative version, the inner core may have a zero or negative hardness gradient, and the outer core layer may have a positive hardness gradient. In yet another embodiment, both the inner core layer and the outer core layer have a zero or negative hardness gradient.
[0050] The core layer has a positive, negative, or zero hardness gradient defined by hardness measurements taken at the outer surface of the inner core (or outer surface of the outer core) and radially inward toward the center of the inner core (or inner surface or midpoint of the outer core). These measurements are typically taken in 2 mm increments, as described in the test methods below. In general, the hardness gradient is determined by subtracting the hardness value of the innermost portion of the component being measured (e.g., the center of the inner core or the midpoint of the outer core layer) from the hardness value of the outer surface of the component being measured (e.g., the outer surface of the inner core or the outer surface of the outer core layer). When one or more core layers surround the layer of interest, it may be difficult to determine the exact midpoint, and therefore, for purposes of this invention, measurements of the "midpoint" hardness of a layer are taken within ±1 mm of the measured midpoint of the layer.
[0051] The inner core preferably has a geometric center hardness (H inner core center ). For example, (H inner core center ) can be within the range of about 5 to about 88 Shore D, and more specifically, can be within the range having a lower limit of about 5 or 10 or 18 or 20 and an upper limit of about 80 or 82 or 84 or 88 Shore D. In other examples, the center hardness (H inner core center ) is preferably about 10 Shore C or more, for example, H inner core center may have a lower limit of about 10, 14, 16, or 20 Shore C and an upper limit of about 78, 80, 84, or 90 Shore C. inner core surface ), the hardness is preferably about 12 Shore D or more, e.g., H inner core surface The hardness of the outer surface of the inner core, as measured in Shore C units, can be within a range having a lower limit of about 12, 15, 18, or 20 and an upper limit of about 80, 84, 86, or 90 Shore D. inner core surface ) has a lower limit of about 13, 15, 18, or 20 Shore C and an upper limit of about 86, 88, 90, or 92 Shore C. In other versions, the geometric center hardness (Hinner core center ) ranges from about 10 Shore C to about 50 Shore C, and the outer surface hardness (H inner core surface ) ranges from about 5 Shore C to about 50 Shore C.
[0052] On the other hand, the outer core layer preferably has an outer surface hardness (H outer surface of OC ), more preferably within a range having a lower limit of about 40 or 42 or 44 or 46 and an upper limit of about 85 or 87 or 88 or 90 Shore D. The outer surface hardness (H outer surface of OC ) preferably has a lower limit of about 40 or 42 or 45 or 48 and an upper limit of about 88 or 90 or 92 or 95 Shore C. And the midpoint hardness (H midpoint of OC ) preferably has a hardness of about 40 Shore D or greater, more preferably about 40 Shore D within a range of about 40 or 42 or 46 or 48 or 50 Shore D and about 80 or 82 or 85 or 88 or 90 Shore D. midpoint of OC ), when measured in Shore C units, the lower limit is about 40 or 42 or 44 or 45 or 47 and the upper limit is about 85 or 88 or 90 or 92 or 95 Shore C.
[0053] The core structure also has a hardness gradient throughout the core assembly. inner core center ) is in the range of about 10 Shore C to about 60 Shore C, preferably about 13 Shore C to about 55 Shore C, (H outer surface of OC ) ranges from about 65 to about 96 Shore C, preferably from about 68 Shore C to about 94 Shore C, providing a positive hardness gradient throughout the core assembly. The total core gradient throughout the core assembly is preferably in the range of about 10 to about 40 units, more preferably in the range of about 15 to about 30 units. In other embodiments, there is a zero or negative hardness gradient throughout the core assembly. For example, the center of the core (H inner core center) may have a hardness gradient ranging from 20 to 90 Shore C, and the outer surface of the outer core may have a hardness gradient ranging from 10 to 80 Shore C. The hardness gradient throughout the core assembly will vary depending on a variety of factors, including but not limited to the dimensions of the inner core, intermediate core, and outer core layers.
[0054] Middle Tier In one preferred embodiment, an intermediate layer is disposed between the single or multiple layer core and the surrounding cover layer. These intermediate layers are sometimes referred to as casing layers or inner cover layers. The intermediate layer may be formed from any material known in the art, including thermoplastic and thermosetting materials, but is preferably formed from an ionomer composition including an ethylene acid copolymer containing acid groups that are at least partially neutralized. Suitable ethylene acid copolymers that can be used to form the intermediate layer are generally referred to as copolymers of ethylene; C3-C8 α,β-ethylenically unsaturated mono- or dicarboxylic acids; and optional softening monomers. These ethylene acid copolymer ionomers can also be used to form the inner and outer core layers as described above.
[0055] Cover Structure As previously mentioned, a golf ball assembly generally includes a core assembly surrounded by a protective cover layer. The ball may include one or more cover layers. For example, golf balls can be made with a single layer cover. In other versions, golf balls can be made with a two-layer cover, including an inner and an outer cover layer.
[0056] The cover layer of the present invention provides the ball with various advantageous mechanical properties, such as, for example, high impact durability and high levels of shear resistance. Additionally, the multi-layer cover, in combination with the core layer, helps to provide the golf ball with high resilience, as will be further described below. In general, the hardness and thickness of the different cover layers may vary depending on the desired ball structure. Additionally, as described above, an intermediate layer may be disposed between the core layer and the cover layer. The cover layer preferably has good impact resistance, toughness, and abrasion resistance.
[0057] Suitable conventional materials that can be used to form the cover layer include, but are not limited to, polyurethanes; polyureas; blends and hybrids of polyurethanes and polyureas; olefin-based copolymer ionomer resins (e.g., Surlyn® ionomer resins and DuPont HPF® 1000, HPF® 2000, HPF® 1035, and HPF® AD1172, available from DuPont; Iotek® ionomers available from Exxon Mobil Chemical Company; Amplify® IO ionomers, ethylene acrylic acid copolymers available from The Dow Chemical Company; and A. Schulman Clarix® ionomer resins available from Arkema Inc.; polyethylenes including, for example, low density polyethylene, linear low density polyethylene, and high density polyethylene; polypropylene; rubber-toughened olefin polymers; acid copolymers that are not part of an ionomeric copolymer, such as poly(meth)acrylic acid; plastomers; flexomers; styrene / butadiene / styrene block copolymers; styrene / ethylene-butylene / styrene block copolymers; dynamically vulcanized elastomers; copolymers of ethylene and vinyl acetate; copolymers of ethylene and methyl acrylate; polyvinyl chloride resins; polyamides, poly(amide-ester) elastomers, and graft copolymers of ionomers and polyamides, such as Pebax® thermoplastic polyether block amides available from Arkema Inc.; crosslinked trans-polyisoprene and blends thereof; Hytrel® or Ticona Engineering available from DuPont. Polyester-based thermoplastic elastomers, such as RiteFlex® available from Polymers; polyurethane-based thermoplastic elastomers, such as Elastollan® available from BASF; synthetic or natural vulcanized rubber; and combinations thereof.Polyurethanes, polyureas, and hybrids of polyurethanes and polyureas are particularly desirable because these materials can be used to produce golf balls that have high resilience and a soft feel. The term "polyurethane and polyurea hybrids" is meant to include copolymers and blends thereof.
[0058] Generally, polyurethanes contain urethane linkages formed by reacting isocyanate groups (-N=C=O) with hydroxyl groups (OH). Polyurethanes are produced by the reaction of multifunctional isocyanates (NCO-R-NCO) with long-chain polyols with terminal hydroxyl groups (OH-OH) in the presence of catalysts and other additives. The chain length of the polyurethane prepolymer is extended by reacting with short-chain diols (OH-R'-OH). The resulting polyurethane has elastomeric properties due to the covalent bonding of the "hard" and "soft" segments. This phase separation occurs primarily due to the incompatibility of the non-polar, low melting soft segments with the polar, high melting hard segments. The hard segments formed by the reaction of diisocyanates with low molecular weight chain extending diols are relatively rigid and immobile. The soft segments formed by the reaction of diisocyanates with long chain diols are relatively flexible and mobile. The hard segments are covalently bonded to the soft segments, which inhibit the plastic flow of the polymer chains and give the elastomer its elasticity.
[0059] Thermoplastic polyurethanes have minimal crosslinking. The polymer network bonds are primarily through hydrogen bonds or other physical mechanisms. Due to the low level of crosslinking, thermoplastic polyurethanes are relatively flexible. The crosslinks in thermoplastic polyurethanes can be reversibly broken by increasing the temperature, such as during molding or extrusion. That is, the thermoplastic material softens when exposed to heat and returns to its original state when cooled. Thermoset polyurethanes, on the other hand, become irreversibly hard when cured. The crosslinks are irreversibly hardened and cannot be broken by exposure to heat. Thus, thermoset polyurethanes, which usually have a high level of crosslinking, are relatively rigid.
[0060] Suitable ionomer compositions include partially neutralized ionomers and highly neutralized ionomers (HNPs), including blends of two or more partially neutralized ionomers, blends of two or more highly neutralized ionomers, and partially neutralized ionomers and one or more highly neutralized ionomers. For the purposes of this disclosure, "HNP" refers to the acid copolymer after at least 70% of the total acid groups present in the composition have been neutralized. Preferred ionomers are salts of O / X- and O / X / Y-type acid copolymers, where O is an α-olefin, X is a C3-C8 α,β-ethylenically unsaturated carboxylic acid, and Y is a softening monomer. O is preferably selected from ethylene and propylene. X is preferably selected from methacrylic acid, acrylic acid, ethacrylic acid, crotonic acid, and itaconic acid. Methacrylic acid and acrylic acid are particularly preferred. Preferred examples of Y include n-butyl (meth)acrylate, isobutyl (meth)acrylate, isobutyl (meth)acrylate, isobutyl (meth)acrylate, (meth)acrylate, and ethyl (meth)acrylate.
[0061] Preferred O / X- and O / X / Y-type copolymers include, but are not limited to, ethylene acid copolymers, such as ethylene / (meth)acrylic acid, ethylene / (meth)acrylic acid / maleic anhydride, ethylene / (meth)acrylic acid, acrylic acid / maleic acid monoester, ethylene / maleic acid, ethylene / maleic acid monoester, ethylene / (meth)acrylic acid / n-butyl (meth)acrylate, ethylene / (meth)acrylic acid / isobutyl (meth)acrylate, ethylene / (meth)acrylic acid / methyl (meth)acrylate, ethylene / (meth)acrylic acid / ethyl (meth)acrylate terpolymers, and the like. The term "copolymer" as used herein includes polymers containing two types of monomers, polymers having three types of monomers, and polymers having more than two types of monomers. Preferred α,β-ethylenically unsaturated mono- or dicarboxylic acids are (meth)acrylic acid, ethacrylic acid, maleic acid, crotonic acid, fumaric acid, itaconic acid. (Meth)acrylic acid is most preferred. As used herein, "(meth)acrylic acid" means methacrylic acid and / or acrylic acid. Similarly, "(meth)acrylate" means methacrylate and / or acrylate.
[0062] In a particularly preferred version, highly neutralized E / X and E / X / Y type acid copolymers are used, where E is ethylene, X is a C3-C8 α,β-ethylenically unsaturated carboxylic acid, and Y is a softening monomer. X is preferably selected from methacrylic acid, acrylic acid, ethacrylic acid, crotonic acid, and itaconic acid. Methacrylic acid and acrylic acid are particularly preferred. Y is preferably an acrylate selected from alkyl acrylates and aryl acrylates, preferably selected from (meth)acrylates and alkyl (meth)acrylates, in which the alkyl group has 1 to 8 carbon atoms, such as n-butyl (meth)acrylate, isobutyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, etc. Preferred E / X / Y type copolymers include those in which X is (meth)acrylic acid and / or Y is (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, etc. More preferred E / X / Y type copolymers are ethylene / (meth)acrylic acid / n-butyl acrylate, ethylene / (meth)acrylic acid / methyl acrylate, and ethylene / (meth)acrylic acid / ethyl acrylate.
[0063] The amount of ethylene in the acid copolymer is typically at least 15% by weight, preferably at least 25% by weight, more preferably at least 40% by weight, and even more preferably at least 60% by weight, in total. The weight of the copolymer is expressed. The amount of C3-C8 α,β-ethylenically unsaturated mono- or dicarboxylic acid in the acid copolymer is typically present in an amount of about 0.1% to about 25% by weight, and even more preferably about 10% to about 20% by weight, based on the total weight of the copolymer, from 1% to 35% by weight, preferably from 5% to 30% by weight, and even more preferably from 5% to 20% by weight. The amount of any softening comonomer in the acid copolymer is typically present in an amount of 0% to 50% by weight, preferably from 5% to 40% by weight, more preferably from 10% to 35% by weight, and even more preferably from 20% to 30% by weight. "Low acid" and "high acid" ionomer polymers as well as blends of such ionomers can be used. Generally, low acid ionomers are considered to contain 16 weight percent or less acid moieties, while high acid ionomers are considered to contain greater than 16 weight percent acid moieties.
[0064] The various O / X, E / X, O / X / Y, and E / X / Y type copolymers are optionally at least partially neutralized with a cation source in the presence of a high molecular weight organic acid, as disclosed, for example, in U.S. Pat. No. 6,756,436, the entire disclosure of which is incorporated herein by reference. The acid copolymer can be reacted with any high molecular weight organic acid and cation source simultaneously or prior to the addition of the cation source. Suitable cation sources include metal ion sources such as compounds of alkali metals, alkaline earth metals, transition metals, and rare earth elements; ammonium salts and monoamine salts; and combinations thereof. Preferred cation sources are compounds of magnesium, sodium, potassium, cesium, calcium, barium, manganese, copper, zinc, lead, tin, aluminum, nickel, chromium, lithium, and rare earth metals.
[0065] Ionomers are usually made by polymerizing monomers that contain free carboxylic acid groups and α-olefins. Then, at least some of the acid groups are neutralized with a metal cation. For example, ethylene and methacrylic acid can be reacted first to form the acid polymer, as shown in the following diagram:
[0066] Preparation of acid polymers [ka]
[0067] An ionomer may then be formed by neutralization by reacting the acidic polymer with a cation source (e.g., a sodium or zinc cation source). For example, the acidic polymer can be reacted with NaOH or ZnCO. In one example, the resulting polymer is the sodium salt, as shown in the following diagram:
[0068] An ionomer may then be formed by neutralization by reacting the acidic polymer with a cation source (e.g., a sodium or zinc cation source). For example, the acidic polymer can be reacted with NaOH or ZnCO. In one example, the resulting polymer is the sodium salt, as shown in the following diagram: Ionomer Production [ka]
[0069] In dual layer cover constructions, where an outer cover layer exists over an inner cover layer, the hardness levels of the cover layers may vary. For example, in a "hard over soft" version, the outer surface hardness of the outer cover layer is preferably greater than the midpoint hardness of the inner cover layer. Alternatively, in a "soft over hard" version, a relatively soft outer cover may be placed around a relatively hard inner cover. As discussed above, compositions including an ionomer or blend of ionomers may be used to form the cover layers.
[0070] If the ball includes an inner cover layer, the hardness (midpoint) is typically about 50 Shore D or greater, more preferably about 55 Shore D or greater, and most preferably about 60 Shore D or greater. In one embodiment, the inner cover has a Shore D hardness of about 62 to about 90 Shore D. In one example, the inner cover has a hardness of about 68 Shore D or greater. Furthermore, the thickness of the inner cover layer is preferably from about 0.015 inch to about 0.100 inch, more preferably from about 0.020 inch to about 0.080 inch, and most preferably from about 0.030 inch to about 0.050 inch.
[0071] The outer cover preferably has a thickness within a range having a lower limit of about 0.004 or 0.010 or 0.020 or 0.030 or 0.040 inches and an upper limit of about 0.050 or 0.055 or 0.065 or 0.070 or 0.080 inches. Preferably, the thickness of the outer cover is about 0.020 inches or less. In some embodiments, the outer cover has a surface hardness of 65 Shore D or less, or 55 Shore D or less, or 50 Shore D or less, or 50 Shore D or less, or 45 Shore D or less. In one example, the outer cover has a hardness ranging from about 20 to about 59 Shore D. In another example, the outer cover has a hardness ranging from about 25 to about 55 Shore D.
[0072] For example, a composition including an ethylene acid copolymer ionomer, such as, for example, Surlin® and Nucrel® (DuPont), can be used to form the cover layer. In another example, a cover layer formed from a composition including a high acid ionomer and a maleic anhydride grafted non-ionomeric polymer can be used. A particularly suitable high acid ionomer is Surlyn 8150®, a copolymer of ethylene and methacrylic acid, having an acid content of 19% by weight, neutralized 45% with sodium. A particularly suitable maleic anhydride grafted polymer is Fusabond 525D® (DuPont). Fusabond 525D® is a maleic anhydride grafted metallocene catalyzed ethylene-butene copolymer, with about 0.9 wt% maleic anhydride grafted onto the copolymer.
[0073] A composition comprising a 50 / 45 / 5 blend of Surlyn® 8940 / Surlyn® 9650 / Nucrel® 960 can be used. In yet another version, the cover layer can be formed from a composition comprising a 50 / 25 / 25 blend of Surlyn® 8940 / Surlyn® 9650 / Surlyn® 9910. A composition comprising a 50 / 50 blend of Surlyn® 8940 / Surlyn® 9650 can also be used. Surlyn® 8940 is an E / MAA copolymer in which the MAA acid groups are partially neutralized with sodium ions. Surlyn® 9650 and Surlyn® 9910 are two different grades of E / MAA copolymer in which the MAA acid groups are partially neutralized with zinc ions. Nucrel® 960 is an E / MAA copolymer resin made with nominally 15 wt% methacrylic acid.
[0074] Nucrel® 9-1 (a copolymer of ethylene and 23.5% n-butyl acrylate, and about 9% unneutralized methacrylic acid); Nucrel® 2940 (a copolymer of ethylene and about 19% unneutralized methacrylic acid); Nucrel® 0403 (a copolymer of ethylene and about 4% unneutralized methacrylic acid); and Nucrel® 960 (a copolymer of ethylene and about 15% unneutralized methacrylic acid). Surlyn® 6320 (a copolymer of ethylene and 23.5% n-butyl acrylate and about 9% methacrylic acid, about 50% neutralized with a magnesium cation source); Surlyn® 8150 (a copolymer of ethylene and about 19% methacrylic acid, about 45% neutralized with a sodium cation source); Surlyn® 8320 (a copolymer of ethylene and 23.5% n-butyl acrylate and about 9% methacrylic acid, about 52% neutralized with a sodium cation source); and Surlyn® 9120 (a copolymer of ethylene and about 19% methacrylic acid, about 36% neutralized with a zinc cation source); and Surlyn® 9320 (a copolymer of ethylene and 23.5% n-butyl acrylate and about 9% methacrylic acid, about 41% neutralized with a zinc cation source). Primacor® 3150, 3330, 5980I, 5986, and 5990I acid copolymers available from The Dow Chemical Company may also be used.
[0075] In one particularly preferred version, a 50% / 50% by weight blend of Surlyn® 8940 (sodium neutralized ethylene acid copolymer ionomer) / 7940 (lithium neutralized ethylene acid copolymer ionomer) is used to form the outer cover layer. Other Surlyn® ionomers include, for example, Surlyn® 9910 (zinc neutralized); Surlyn® 7930 (lithium neutralized). Surlyn® 8940 is a copolymer of ethylene and methacrylic acid with about 15 weight percent acid neutralized with about 29% sodium ions. The resin has an average melt flow index of about 2.8. Surlyn® 9910 is a copolymer of ethylene and methacrylic acid with about 15 weight percent acid neutralized with about 58% zinc ions. Surlyn® 9910 has an average melt flow index of about 0.7. Surlyn® 7930 and Surlyn® 7940 are two similar lithium neutralized poly(ethylene-methacrylic acid) ionomers with different melt indices.
[0076] Golf Ball Construction The inner core can be formed by any suitable technique, including compression and injection molding techniques. The outer core layer, which surrounds the inner core, is formed by molding a composition onto the inner core. Compression or injection molding techniques can be used to form the other layers of the core assembly. A cover layer is then applied to the core assembly. Prior to this step, the core structure can be surface treated to enhance adhesion between its outer surface and the next layer applied onto the core. Such surface treatments can include mechanically or chemically polishing the outer surface of the core. For example, the core can be subjected to corona discharge, plasma treatment, silane dipping, or other treatment methods known to those skilled in the art.
[0077] The cover layers are formed over the core or ball subassembly (the core structure and any intermediate layers disposed about the core) using any suitable technique, such as, for example, compression molding, flip molding, injection molding, retractable pin injection molding, reaction injection molding (RIM), liquid injection molding, casting, spraying, powder coating, vacuum forming, flow coating, dipping, spin coating, etc. Preferably, each cover layer is formed separately over the ball subassembly.
[0078] Conventional compression and injection molding and other methods can be used to form the cover layer on the core or ball subassembly. In general, compression molding involves making a half (hemispherical) shell, usually by injection molding a composition in an injection mold. This produces a semi-hard semi-hard half shell (or cup). The half shell is then placed in a compression mold around the core or ball subassembly. Heat and pressure are applied, fusing the half shells to form the cover layer on the core or subassembly. Compression molding can also be used to cure the cover composition after injection molding. For example, a thermosetting composition can be injection molded around the core in an unheated mold. After the composition is partially cured, the ball is removed and placed in a compression mold. Heat and pressure are applied to the ball, which causes the outer cover layer to heat cure.
[0079] The retractable pin injection molding (RPIM) method can be used to manufacture thermoplastic covers, including ethylene acid copolymer ionomer covers and thermoplastic polyurethane covers, and generally involves the use of upper and lower mold cavities that interlock together. The upper and lower mold cavities form a spherical interior cavity when joined together. The mold cavity used to form the outer cover layer has an interior dimple cavity detail. The cover material conforms to the interior shape of the mold cavity to form the dimple pattern on the surface of the ball. The injection mold includes retractable support pins located throughout the mold cavity. The retractable support pins move in and out of the cavity. The support pins help maintain the position of the core or ball subassembly while the molten composition flows through the mold gate. The molten composition flows into the cavity between the core and the mold cavity, surrounding the core and forming the cover layer. Other methods can be used to fabricate the cover including, for example, reaction injection molding (RIM), liquid injection molding, casting, spraying, powder coating, vacuum forming, flow coating, dipping, spin coating, and the like.
[0080] In a typical thermoset polyurethane casting process, the polyurethane prepolymer and curing agent can be mixed with an electric mixer in a mix head by metering the amount of curing agent and prepolymer through supply lines. The preheated lower mold cavity can be filled with a mixture of reactive polyurethane and curing agent. Similarly, the preheated upper mold cavity can be filled with the reactive mixture. The lower and upper mold cavities are filled with substantially the same amount of reactive mixture. After the reactive mixture has resided in the lower mold cavity for a sufficient time, the golf ball subassembly can be lowered at a controlled rate into the reactive mixture. The ball cup can hold the subassembly by applying a reduced pressure (or partial vacuum). After sufficient gelling, the vacuum can be released to release the subassembly. The upper mold half can then be mated with the lower mold half. An exothermic reaction occurs as the polyurethane prepolymer and curing agent are mixed, which continues until the material solidifies around the subassembly. The molded ball can then be cooled in the mold and removed when the molded cover layer is hard enough to be handled without deformation.
[0081] As discussed above, an inner cover layer or intermediate layer, preferably formed from an ethylene acid copolymer ionomer composition, can be formed between the core or ball subassembly and the cover layer. The intermediate layer including the ionomer composition may be formed using conventional techniques such as compression or injection molding. For example, the ionomer composition may be injection molded or placed into a compression mold to produce half shells. These shells are placed around the core in a compression mold and the shells are fused to form the intermediate layer. Alternatively, the ionomer composition is injection molded directly onto the core using a retractable pin injection mold.
[0082] Primer and topcoat application After the golf balls are removed from the mold, they may be subjected to finishing steps such as flash trimming, surface treatment, marking, and application of coatings in accordance with the present invention.
[0083] For example, in a conventional white golf ball, the outer cover layer containing a white pigment may be surface treated using a suitable method, such as, for example, corona, plasma, or ultraviolet (UV) light treatment. In an alternative finishing process, the golf ball is painted with one or more paint coatings. For example, a white or clear primer paint may be first applied to the surface of the ball, and then a mark may be made on top of the primer before a clear polyurethane topcoat is applied. Indicia such as trademarks, symbols, logos, lettering, etc. may be printed onto the outer cover or primecoat layer or topcoat layer using pad printing, inkjet printing, dye sublimation, or other suitable printing methods. Any of the surface coatings may include an optical brightener.
[0084] Test Method hardness The central hardness of the core is obtained according to the following procedure: The core is gently pressed into a hemispherical holder with an inside diameter approximately slightly smaller than the diameter of the core, while the core is placed in the hemispherical holder and the geometric center surface of the core is exposed. The core is secured in the holder by friction to prevent it from moving during the cutting and scraping steps, yet the friction is not excessive so that the natural shape of the core is not disturbed. The core is mounted so that the parting line of the core is approximately parallel to the top of the holder. The diameter of the core is measured at an 80 degree angle to this orientation prior to mounting. Additionally, a measurement is also made from the bottom of the holder to the top of the core, which provides a reference point for future calculations. The distance from the bottom of the holder to the top of the core is also measured to obtain a reference point for future calibrations. A rough cut is made with a band saw or other suitable cutting tool slightly above the exposed geometric center of the core, while preventing the core from moving in the holder during this step. The remaining part of the core, still held in the holder, is fixed to the base plate of the surface grinder. The exposed "rough" core surface is ground to a smooth, flat surface to reveal the geometric center of the core, which can be verified by measuring the height from the bottom of the holder to the exposed surface of the core. This ensures that exactly half of the original height of the core has been removed to within 0.004 inches. With the core held in the holder, the center of the core is found with a centering ruler, carefully marked, and the hardness is measured at this center mark in accordance with ASTM-D2240. Hardness measurements at any distance from the center of the core are made by drawing a line extending radially outward from the center mark and measuring the hardness at distances typically in 2 mm increments from the center. The hardness at a particular distance from the center should be measured on at least two, and preferably four, radial line segments spaced 180° or 90° apart, respectively, and then averaged. Although all hardness measurements are performed on a plane passing through the geometric center, the core is still in the holder so that its orientation is not disturbed and the measurement surface is always parallel to the bottom of the holder and therefore accurately aligned with the feet of the durometer.
[0085] The hardness of the outer surface of a golf ball layer is measured on the actual outer surface of that layer, taken from the average of multiple measurements taken from opposing hemispheres, taking care not to measure over core parting lines or surface imperfections such as holes or protrusions. Hardness measurements are made in accordance with ASTM D-2240, "Durometer Indentation Hardness of Rubber and Plastics." Due to curved surfaces, care must be taken to center the golf ball or golf ball assembly directly under the durometer indenter before the surface hardness reading is taken. A calibrated digital durometer capable of reading to 0.1 units is used for hardness measurements. The digital durometer should have its feet parallel and be mounted to the base of an automatic stand. The weight on the durometer and the attack speed must comply with ASTM D-2240.
[0086] In some embodiments, the point or points measured along a "positive" or "negative" gradient may be above or below a line fit to the gradient, and may be its outermost and innermost values. In other preferred embodiments, the hardest point along a particular steep "positive" or "negative" gradient may be greater than the value of the innermost portion of the inner core (i.e., the geometric center) or the outer core layer (the inner surface), but the outermost point (i.e., the outer surface of the inner core) must be greater (when "positive") or less (when "negative") than the innermost point (i.e., the geometric center of the inner core or the inner surface of the outer core layer) to keep the "positive" and "negative" gradients intact.
[0087] As discussed above, the direction of the hardness gradient of a golf ball layer is defined by the difference in hardness measurements taken at the outer and inner surfaces of a particular layer. The center hardness of the inner core and the hardness of the outer surface of the inner core or outer core layer of a single core ball are readily determined according to the test procedures described herein. The outer surface of the inner core layer (or other optional intermediate core layer) of a dual core ball is also readily measured according to the procedures described herein for measuring the outer surface of a golf ball layer, provided that the measurements are made before the layer is surrounded by the additional layer. Once the layer of interest is surrounded by the additional core layer, it would be difficult to determine the hardness of the inner or outer surface of any inner or intermediate layer. Therefore, for the purposes of this invention, the test procedures described herein are employed to measure the hardness of the inner or outer surface of a core layer after the inner layer has been surrounded by another core layer, when necessary, at 1 mm from the interface.
[0088] It should also be noted that there is a fundamental difference between "material hardness" and "hardness measured directly on a golf ball." For the purposes of this description, material hardness is measured according to ASTM D2240 and generally refers to measuring the hardness of a flat "slab" or "button" made from a material. It should be understood that "material hardness" and "hardness measured directly on the surface of a golf ball" are fundamentally different. Hardness as measured directly on the surface of a golf ball (or other spherical surface) typically results in a hardness value that is different from material hardness. This difference in hardness value comes from several factors, such as, but not limited to, ball construction (i.e., type of core, number of core and / or cover layers, etc.), ball (or sphere) diameter, and material composition of each adjacent layer. It should also be understood that the two measurement methods do not correlate linearly, and therefore, one hardness value cannot be easily correlated to the other hardness value. Shore C hardness (e.g., Shore C or Shore D hardness) was measured with test method D-2240.
[0089] compression As disclosed in Jeff Dalton's Compression by Any Other Name, Science and Golf IV, Proceedings of World Science Congress of Golf (Eric Thain ed., Routledge, 2002) ("J. Dalton"), several different techniques are used to measure compression, including Atti compression, Riehle compression, load / deflection measurements at various fixed loads and offsets, load / deflection measurements at various fixed loads and offsets, and effective modulus. For purposes of this invention, "compression" refers to the Soft Center Deflection Index ("SCDI"). The SCDI is a program modification to a Dynamic Compression Machine ("DCM") that allows one to determine the pounds required to deflect 10% of the core's diameter. The DCM is a device that applies a load to a core or ball and measures the number of inches the core or ball displaces at a measured load. A raw load / deflection curve is generated that fits the Atti compression scale, which results in a numerical value that indicates the Atti compression. The DCM does this with a load cell attached to the bottom of a hydraulic cylinder that is pneumatically triggered at a fixed rate (typically 1.0 ft / s) toward the stationary core. The cylinder is fitted with an LVDT that measures the distance the cylinder travels during the test time frame. A software-based logarithmic algorithm ensures that no measurements are taken early in the test until at least 5 consecutive load increments have been detected. The SCDI is a slight variation of this setup. The hardware is the same, but the software and output have changed. In the SCDI, the magnitude is the number of pounds of force times the number of inches required to bend the core. The amount of core deflection is 10% of the core diameter. The DCM is triggered, the cylinder deforms the core by 10% of the diameter, and the DCM returns the pounds of force required (measured from the attached load cell) and deflects the core by that amount. The displayed value is a single number in 1 pound units.
[0090] Coefficient of Restitution ("COR") The COR is determined by a known procedure, where a golf ball or golf ball subassembly (e.g., a golf ball core) is launched from an air cannon at two predetermined velocities and the COR is calculated at the velocity of 125 ft / s. A number of ballistic light screens are placed between the air cannon and a steel plate at fixed distances to measure the ball velocity. As the ball travels to the steel plate, each light screen is activated and the time at each light screen is measured. This gives an incoming transit time inversely proportional to the incoming velocity of the ball. The ball impacts the steel plate and rebounds through the light screens and the time interval it takes to transition between the light screens is measured. This gives an outgoing transit time inversely proportional to the outgoing velocity of the ball. The COR is calculated as the ratio of the outgoing transit time interval to the incoming transit time interval, COR=Vout / Vin=Tin / Tout.
[0091] It should be understood that the methods of manufacture, compositions, structures and articles of manufacture described and illustrated herein only represent some embodiments of the present invention. It will be understood that those skilled in the art can make various modifications and additions to the compositions, structures and articles of manufacture without departing from the spirit and scope of the present invention. It should be noted that all such embodiments are intended to be encompassed by the appended claims.
Claims
1. In the golf ball, i) a core assembly; and ii) a cover having at least one layer; The core assembly includes: a) an inner core having a thermoset or thermoplastic composition, the inner core having an inner core diameter (ICD) ranging from 1.2 to 1.5 inches (3.05 to 3.81 cm), an outer surface hardness (H inner core surface ), center hardness (H inner core center ), an inner core volume (ICV), and an inner core compression (ICC); b) an outer core layer having a thermoset or thermoplastic composition disposed about said inner core, said outer core layer having a thickness ranging from 0.05 to 0.2 inches such that said core assembly has a total core diameter (TCD) of between 1.5 and 1.6 inches; The outer core layer has an outer surface hardness (H outer surface of OC ), center point hardness (H midpoint of OC ), outer core layer volume (OCV), and core assembly compression (TCC); the ICV is greater than the OCV, and the core assembly has a core profile between 3.27 and 3.90; (Inner Core Diameter / Core Assembly Diameter) x (Core Assembly Compression / Inner Core Compression) = Core Profile and the inner core and the outer core layer each have a rubber composition selected from the group consisting of polybutadiene, polyisoprene, ethylene-propylene, ethylene-propylene-diene, styrene-butadiene, and polyalkenamer rubbers, and mixtures thereof; H inner core surface Is H inner core center to achieve a greater positive hardness gradient across the inner core, and outer surface of OC H midpoint of OC so as to achieve a greater positive hardness gradient across the outer core layer; H outer surface of OC H inner core center A golf ball characterized in that it achieves a greater positive hardness gradient across the core assembly.
2. The OCV has a value less than or equal to a value X, where X is Formula: (0.9)(ICV)=X 2. The golf ball of claim 1, wherein the average surface area is calculated by the following formula:
3. The TCC has a value greater than or equal to a value Y, where Y is Formula: (2.0)(ICC)=Y 2. The golf ball of claim 1, wherein the average surface area is calculated by the following formula:
4. 2. The golf ball of claim 1, wherein the positive hardness gradient across the core assembly ranges from 15 to 30.
5. 2. The golf ball of claim 1, wherein the inner core comprises 60% of the total volume of the core assembly.
6. 2. The golf ball of claim 1, wherein the inner core comprises 70% of the total volume of the core assembly.
7. 2. The golf ball of claim 1, wherein the inner core has a diameter of 1.39 inches and the core assembly has a diameter of 1.55 inches.
8. 2. The golf ball of claim 1, wherein the inner core has a diameter of 1.25 inches and the core assembly has a diameter of 1.55 inches.
9. 2. The golf ball of claim 1, wherein the inner core has a compression in the range of 20-50 and the core assembly has a compression in the range of 60-110.
10. 2. The golf ball of claim 1, wherein the cover is a single layer and comprises an ethylene acid copolymer containing acid groups such that less than 70% of the acid groups are neutralized.
11. 11. The golf ball of claim 10, wherein the cover comprises a blend of a sodium neutralized ethylene acid copolymer and a lithium neutralized ethylene acid copolymer.
12. 2. The golf ball of claim 1, wherein the cover comprises an inner cover layer and an outer cover layer, the inner cover layer comprising an ethylene acid copolymer containing acid groups such that less than 70% of the acid groups are neutralized, and the outer cover layer comprising a polymer selected from the group consisting of polyurethanes, polyureas, polyurethane-urea hybrids, and copolymers and blends thereof.
13. 13. The golf ball of claim 12, wherein the outer cover layer comprises a thermoplastic polyurethane.
14. 13. The golf ball of claim 12, wherein the outer cover layer comprises a thermoset polyurethane.
Citation Information
Patent Citations
Multi-piece solid golf ball
JP2005152397A
Highly-neutralized thermoplastic copolymer center for improved multi-layer core golf ball
JP2008023342A
Multi-layer golf ball provided with cover layer with increased moisture resistance
JP2008114069A
Multi-layer golf ball
JP2009000520A
Multi-layer golf ball
JP2009219871A